Clinicopathological and imaging features of struma ovarii: a retrospective study - Mei Chen; Shusheng Liao; Youfeng Xu; Xianwang Ye; Xiupeng Jia; Shengmin Zhang (Frontiers in Oncology)
ObjectivesThe struma ovarii (SO) is a rare disease, presenting significant challenges in achieving an accurate diagnosis. This study aims to delineate the clinicopathological and multimodal imaging characteristics of SO, enabling the precise diagnosis of this entity.MethodsA retrospective analysis was conducted of the clinicopathological manifestations, laboratory examination results, and imaging data (including ultrasound and MRI) of 40 SO patients who received treatment at the First Affiliated Hospital of Ningbo University over the period from January 2010 to February 2024.ResultsThe pathological results of 40 patients showed 21 pure SO, including 20 benign and one malignant; 19 patients had mixed SO, composed of 17 benign and two malignant. Three malignant cases were thyroid carcinoid. According to the ultrasound image, 40 SO patients were divided into three types: 22 cases were cystic, which had mainly single room or separations; 12 cases were mainly cystic-solid mixed, which had multiple septations and hyperechoic nodules; and six solid cases showed regular or irregular mass and rich blood supply. Five patients underwent contrast-enhanced ultrasound (CEUS) examination. The cystic wall and septation showed equal enhancement and slow regression. Two patients showed low enhancement in the protrusion and with slow regression. The MRI manifestations of SO are various. In this cohort, T1-weighted imaging (T1WI) showed hypo-intensity in six cases and heterogeneity in six cases; T2-weighted imaging (T2WI) showed hypo-intensity in two cases, heterogeneity in five cases, and hyper-intensity in four cases; diffusion-weighted imaging (DWI) showed hypo-intensity in two cases, heterogeneity in three cases, and hyper-intensity in four cases.ConclusionsThe incidence of SO is low, but there are some features in imaging. There were cystic, cystic-solid, or solid lesions in the appendage area; CEUS showed separations and solid components with rich blood flow and slow enhancement; MRI showed high signal on T2WI and multiple cysts and heterogeneous signal on T1WI, which were the imaging markers for SO. A comprehensive understanding of imaging manifestations can help radiologists identify this disease and provide a basis for an appropriate therapeutic regime.